求证:(x^2-xy+y^2)^3+(x^2+xy+y^2)^3能被2x^2+2y^2整除
人气:218 ℃ 时间:2019-10-31 14:32:48
解答
有公式
a³+b³=(a+b)(a²-ab+b²)
故
(x^2-xy+y^2)^3+(x^2+xy+y^2)^3
=(x^2-xy+y^2+x^2+xy+y^2)((x^2+xy+y^2)^2-(x^2-xy+y^2)*(x^2+xy+y^2)+(x^2+xy-y^2)^2)
=(2x^2+2y^2)((x^2+xy+y^2)^2-(x^2-xy+y^2)*(x^2+xy+y^2)+(x^2+xy-y^2)^2)
有因式2x^2+2y^2
因此
(x^2-xy+y^2)^3+(x^2+xy+y^2)^3能被2x^2+2y^2整除
推荐
- (xy-3/2y-1/2)-(xy-3/2x+1),其中x=10/3,y=8/3.,急啊.
- 已知x-y=1,x*y=3 求x^3y-2x^2y^2+xy^3的值.
- 化简-x∧3-xy∧2+ 2x∧2y/x∧3-y∧2x
- 已知xy分之x+y=3,求-x+2y-y分之2x-3xy+2y的值.
- 已知x-y=6,xy=-2,求3(xy+x-2y)-5(y-2x)+2(xy-x)的值.
- 做一个长方体形状的鱼缸,长8分米,宽3分米,需要玻璃多少平方分米?
- Every boring hour in life is unique
- 英语翻译
猜你喜欢